Effects of homocysteine on nonalcoholic fatty liver related disease: A mendelian randomization study - Chen, Pengcheng; Yang, Ze; Guo, Lingyun; Huang, Yingfei; Li, Jingjia; Chen, Xin (Frontiers in Molecular Biosciences, 2022)
Background: Since the association of homocysteine and clinical results of observational studies are controversial on non-alcoholic fatty liver related disease, we compute the two-sample Mendelian Randomization (MR) study. Objective: To evaluate whether the plasma level of homocysteine has an effect on the risk of Non-alcoholic fatty liver disease (NAFLD), nonalcoholic steatohepatitis (NASH), and Cirrhosis after its progress, we investigated the causal relationships between plasma homocysteine and the three non-alcoholic fatty liver related diseases mentioned above. Design and Methods: Summary estimates were elicited from the inverse-variance weighted (IVW) method through 12 single nucleotide polymorphisms (SNPs) which related to the plasma homocysteine, the SNPs were obtained from a large genome-wide association study (GWAS) of 44,147 European participants. And the summary statistics for the latest and largest GWAS datasets for NAFLD (307576 in total and 1578 cases), NASH (309055 in total and 99 cases) and Cirrhosis (306145 in total and 826 cases) were collected from Ristey FinnGen website where the association of genetic variations with blood metabolite levels was conducted using comprehensive metabolite profiling. The study was performed through two-sample MR method. Results: The result indicated that the plasma homocysteine is not significantly associated with NAFLD, and its progression, NASH and Cirrhosis. Conclusion: The evidence in this study is quite deficient to support the causal association of the individual plasma homocysteine with NAFLD, NASH and Cirrhosis, the putative of associations is not exist.